Lending Relationships, Borrowing Costs and Crisis: Evidence from Indian Micro Data. Issue 4 (August 2019) - Ghosh, Saibal
Abstract: The analysis employs data on Indian listed firms from 1996 to 2010 to explore several hypotheses relating to the costs of lending relationships. The evidence indicates that smaller, established, levered and high-growth firms charge higher interest rates. In addition, capitalized firms charge lower rates, and both bank and firm ownership do have a role to play in influencing borrowing costs.